AIDS FOR TEACHING SCIENCE: EVIDENCES OF A GOOD SCIENCE PROGRAM. (Science Education, 1964)
The article offers information about characteristics of a good science program in the U.S. The good science program enable teachers to participate in formulating the overall objectives of instruction. The need for the evidences of purposeful planning leading to the attainment of the objectives. It enhances the natural curiosity of boys and girls. It provides continual practice in the use of skills associated with the process of scientific inquiry.